Forest conservation in the Anthropocene : science, policy, and practice - Miller, Char, 1951-; Bixler, R. Patrick (Richard Patrick); Sample, V. Alaric (University Press of Colorado, 2016)
"Thought-provoking insight on overcoming the constraints of climate change and policies that need to be introduced or changed to combat the climate change on the forests of the world. Environmental scientists probe the dilemmas that confront us and will continue to confront us in the coming century"--